Digital Literacy Profile of Prospective Elementary School Teachers in Indonesian Language Learning: a Case Study at Universitas Muhammadiyah Prof. DR. HAMKA - Nur Latifah; Septi Fitri Meilin; Silvie Mil; Sa'odah Sa'odah (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractDigital literacy is essential for Prospective Elementary School Teachers to foster the development of technology-based teaching skills. Therefore, understanding the digital literacy profile of prospective is essential as a foundation for developing informed learning policies. This study aims to describe the digital literacy profiles of prospective elementary school teachers by analyzing their digital literacy skills through a quantitative survey-based research approach. The study population consisted of 1,400 students, from which a sample of 210 was selected using stratified random sampling. The research instrument consisted of a Likert-scale questionnaire encompassing indicators such as functional and technical skills in operating digital devices, creativity in producing digital learning content, collaboration abilities using digital platforms, communication skills within digital spaces, information literacy in locating and selecting learning resources, critical thinking in evaluating digital content, socio-cultural awareness related to digital ethics, electronic security in safeguarding personal data, and technical problem-solving competencies. The study’s findings indicated that prospective of elementary school strong proficiency in information literacy, with an average score of 4.57, and digital communication, scoring 4.42. However, certain areas require further development, particularly electronic security (3.50) and digital socio-cultural understanding (3.65), which received comparatively lower scores. In light of these findings, measures should be taken to enhance the digital literacy of prospective primary school teachers, particularly through language skills courses aimed at strengthening their understanding and effective use of digital technology and information.Keywords: digital literacy, Indonesian language learning, prospective elementary school.AbstrakLiterasi digital sangat penting bagi Calon Guru Sekolah Dasar untuk mendorong pengembangan keterampilan mengajar berbasis teknologi. Oleh karena itu, memahami profil literasi digital calon guru sangat penting sebagai dasar untuk mengembangkan kebijakan pembelajaran yang terinformasi. Penelitian ini bertujuan untuk mendeskripsikan profil literasi digital calon guru sekolah dasar dengan menganalisis keterampilan literasi digital mereka melalui pendekatan penelitian berbasis survei kuantitatif. Populasi penelitian terdiri dari 1.400 siswa, dengan sampel sebanyak 210 siswa dipilih secara acak. Instrumen penelitian terdiri dari kuesioner skala Likert yang mencakup indikator-indikator seperti keterampilan fungsional dan teknis dalam mengoperasikan perangkat digital, kreativitas dalam menghasilkan konten pembelajaran digital, kemampuan berkolaborasi menggunakan platform digital, keterampilan komunikasi dalam ruang digital, literasi informasi dalam menemukan dan memilih sumber belajar, berpikir kritis dalam mengevaluasi konten digital, kesadaran sosial budaya terkait etika digital, keamanan elektronik dalam menjaga data pribadi, dan kompetensi pemecahan masalah teknis. Temuan penelitian menunjukkan bahwa calon guru sekolah dasar memiliki kecakapan yang kuat dalam literasi informasi, dengan skor rata-rata 4,57, dan komunikasi digital, dengan skor 4,42. Namun, beberapa area perlu dikembangkan lebih lanjut, terutama keamanan elektronik (3,50) dan pemahaman sosial budaya digital (3,65), yang mendapatkan skor relatif lebih rendah. Berdasarkan temuan ini, langkah-langkah perlu diambil untuk meningkatkan literasi digital calon guru sekolah dasar, terutama melalui kursus keterampilan berbahasa yang bertujuan memperkuat pemahaman dan penggunaan teknologi dan informasi digital secara efektif.Kata kunci: literasi digital, pembelajaran bahasa indonesia, calon guru sekolah dasar.